Pentingnya unsur hara fosfor untuk pertumbuhan tanaman padi - Maulidan, Khopid; Putra, Bayu Karunia (Journal of Biopesticides and Agriculture Technology, 2024)
Background: The need for carbohydrates for our bodies makes rice a staple food, especially for the Indonesian people. The increasing population means that the need for food will certainly continue to increase. So in this case, increasing rice production is certainly very important to do in order to meet the needs of the population. Findings: Phosphorus makes up about 0.2% of the dry weight of plants, and plants will not grow if this element is not sufficient. Phosphorus plays a role in the circulation of energy in plants, which is obtained from photosynthesis, respiration, and carbohydrate metabolism in the form of ATP and ADP. In addition, phosphorus also has the property of easily reacting with soil and easily binding to other compounds (Al and Fe), so that the P element cannot be utilized by plants. Methods: This paper uses a literature study method, which is sourced from literature such as scientific articles, books, journals, and online media. Conclusion: Phosphorus nutrients are very important for plant growth which is an essential element for plants because it is a limiting factor that affects plant growth and production. In rice plants, the element P plays a role in encouraging the growth and formation of panicles, triggering flowering and fruit ripening especially in low climate conditions, encouraging more clump/tiller formation which allows faster recovery and adaptation when rice plants experience stress, and supporting the formation of better grain and having better nutritional content in relation to the P content in the seeds.